Comparative cardiovascular safety of glucagon‐like peptide‐1 receptor agonists versus other antidiabetic drugs in routine care: a cohort study. Issue 8 (2nd May 2016) - Patorno, E.; Everett, B. M.; Goldfine, A. B.; Glynn, R. J.; Liu, J.; Gopalakrishnan, C.; Kim, S. C.
Abstract : Aims: To evaluate the comparative cardiovascular disease (CVD) safety of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) in head‐to‐head comparisons with dipeptidyl peptidase‐4 (DPP‐4) inhibitors, sulphonylureas or insulin, when added to metformin, as used in 'real‐world' patients with type 2 diabetes mellitus (T2DM). Methods: Within a large US commercial health plan database linked to laboratory test results, we identified three pairwise 1 : 1 propensity‐score‐matched cohorts of patients with T2DM aged ≥18 years treated with metformin who initiated a GLP‐1 RA or a comparator, i.e. DPP‐4 inhibitor (n = 35 534), second‐generation sulphonylureas (n = 28 138) or insulin (n = 47 068), between 2005 and 2013. We examined the association between drug initiation and a composite CVD endpoint, comprising hospitalizations for acute myocardial infarction, unstable angina, stroke or coronary revascularization. Results: During the course of 1 year, there were 13.9 and 13.7 CVD events per 1000 person‐years among propensity‐score‐matched initiators of GLP‐1 RAs versus DPP‐4 inhibitors [hazard ratio (HR) 1.02; 95% confidence interval (CI) 0.84–1.24]; and 12.1 versus 14.0 events among initiators of GLP‐1 RAs versus sulphonylureas (HR 0.86; 95% CI 0.69–1.08). The effect estimates for GLP‐1 RAs versus insulin were sensitive to the adjustment for glycated haemoglobin, after which the HR was 1.01 (95% CI 0.73–1.41). Results were robust across several sensitivity analyses, including an as‐treated analysis considering up to 8.7 years of follow‐up. Conclusions: This large study, performing head‐to‐head comparisons of GLP‐1 RAs with other antidiabetic agents in real‐world patients, provides estimates of relative safety precise enough to exclude large differences in CVD risk and adds further understanding to results from recent clinical trials.